Gastricsin in the benign and malignant prostate. Issue 6 (June 1985) - Reid, W A; Liddle, C N; Svasti, J; Kay, J
Abstract : An immunoperoxidase (peroxidase-antiperoxidase) method was used to localise the gastric acid proteinase gastricsin in prostate. The enzyme was present, probably as zymogen, in acinar lining cells in 66 (69%) of 96 cases of benign prostatic enlargement; other normal tissues from male genital tract were negative. It was also present in the tumour cells in 21 (39%) of 54 cases of prostatic adenocarcinoma. The findings support the suggestion that the prostate is the source of the gastricsin of normal seminal fluid. It is not yet clear whether its presence in prostatic carcinomas will be of diagnostic use.